2018
DOI: 10.1002/etc.4129
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance tests as a tool to detect sublethal effects of oil‐impacted sediments

Abstract: Currently, risk assessment for oil contamination does not consider behavioral responses of benthos to oil toxicity. Avoidance of oil-contaminated sediment by benthic amphipods, however, may be a highly sensitive endpoint for sublethal effects of commonly used distillate fuels. In the present study, the avoidance behavior of temperate freshwater (Gammarus pulex) and marine (Gammarus locusta) amphipods was tested by allowing them to choose between a reference sediment and a distillate marine grade A (DMA) oil-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…The present study only concerned acute, narcotic effects; and it should be noted that oil can also cause adverse effects by smothering organisms, by inducing specific toxicity, or by causing sublethal effects upon chronic exposure to low concentrations (Stark et al, 2017;Szczybelski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study only concerned acute, narcotic effects; and it should be noted that oil can also cause adverse effects by smothering organisms, by inducing specific toxicity, or by causing sublethal effects upon chronic exposure to low concentrations (Stark et al, 2017;Szczybelski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For the experiments conducted at temperate conditions, the amphipod G. locusta was used. This species lives on sediment and macrophytes, occurs on west European coasts (Costa et al, 2004), and is frequently used in eco(toxico)logical research (see Szczybelski et al, 2018). Organisms were collected in the intertidal area at two sites in the Oosterschelde, The Netherlands (Goese Sas [51°32′43.36″N, 3°55′28.79″E] and Kattendijke [51°31′45.71″N, 3°57′57.07″E]), between March and June 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, various studies have shown that amphipods significantly avoid contaminated sediments in a concentration dependent manner (Hellou et al, 2005;De Lange et al, 2006;Szczybelski et al, 2018). Therefore, G. locusta possibly avoided pure olivine due to its high Ni (38 µmol g -1 d.w.) and Cr (23 µmol g -1 d.w.) content (Table 5.1) in order to reduce trace metal exposure (Araújo et al, 2016).…”
Section: Avoidance Behaviourmentioning
confidence: 99%
“…Thompson et al, 2007;Szczybelski et al 2018). 1.1.3.4 Plastic pollutionHarm caused by heavy metals, PAHs and other POPs can be inflated by the presence of plastic particles that may act as a vector(Qui et al, 2015;Akhbarizadeh et al, 2017;Ferreira et al, 2019;Yazdani-Foshtomi et al, 2019).…”
mentioning
confidence: 99%